NUTRITIONAL COMPOSITION AND ANTIOXIDANT CAPACITY OF THREE SPECIES OF SACHA INCHI Plukenetia spp. FROM PERUVIAN AMAZON - BARDALES ARÉVALO, Jak (2019)
Chemical composition and antioxidant activity of three species of sacha inchi seeds (Plukenetia voluvilis, Plukenetia carolis-vegae and Plukenetia huayllabambana) were evaluated and compared. The analyzes of proximal composition, analysis of micro and macro nutrients, physicochemical properties and fatty acid composition of the oils, and the evaluation of the antioxidant activity using the methods of DPPH and ABTS were performed. The results showed a similarity between P. carolis-vegae and P. huayllabambana, these species had a high oil content (49.28 and 48.82%, respectively) compared to P. voluvilis (34.23%). The three species presented a similar fatty acid profile, with linolenic acid (omega-3) being the majority (48.32-58.71%). In the mineral content, potassium was the most predominant in P. carolis-vegae and P. huayllabambana (686.04 and 710.69 mg / 100g, respectively), unlike P. voluvilis which was calcium (237, 92 m / 100g). P. carolis-vegae was the species that presented the highest antioxidant activity (DPPH 2.30 µmol TE/g, ABTS 3.38 µmol TE/g) and correlated with its total phenolic content (3.85 mg AG / 100g). These results indicate that P. carolis-vegae could also be used by the food and pharmaceutical industry as P. voluvilis, because it presents better nutritional properties.